A survey of Fusarium species and ADON genotype on Canadian wheat grain - Bamforth, Janice; Chin, Tiffany; Ashfaq, Tehreem; Gamage, Niradha Withana; Pleskach, Kerri; Tittlemier, Sheryl A.; Henriquez, Maria Antonia; Kurera, Shimosh; Lee, Sung-Jong; Patel, Bhaktiben; Gräfenhan, Tom; Walkowiak, Sean (Frontiers in Fungal Biology, 2022)
Wheat is a staple food that is important to global food security, but in epidemic years, fungal pathogens can threaten production, quality, and safety of wheat grain. Globally, one of the most important fungal diseases of wheat is Fusarium head blight (FHB). This disease can be caused by several different Fusarium species with known differences in aggressiveness and mycotoxin-production potential, with the trichothecene toxin deoxynivalenol (DON) and its derivatives being of particular concern. In North America, the most predominant species causing FHB is F. graminearum, which has two distinct sub-populations that are commonly classified into two main chemotypes/genotypes based on their propensity to form trichothecene derivatives, namely 15-acetyldeoxynivalenol (15-ADON) and 3-acetyldeoxynivalenol (3-ADON). We used a panel of 13 DNA markers to perform species and ADON genotype identification for 55, 444 wheat kernels from 7, 783 samples originating from across Canada from 2014 to 2020. Based on single-seed analyses, we demonstrate the relationships between Fusarium species and trichothecene chemotype with sample year, sample location, wheat species (hexaploid and durum wheat), severity of Fusarium damaged kernels (FDK), and accumulation of DON. Results indicate that various Fusarium species are present across wheat growing regions in Canada; however, F. graminearum is the most common species and 3-ADON the most common genotype. We observed an increase in the occurrence of the 3-ADON genotype, particularly in the western Prairie regions. Our data provides important information on special-temporal trends in Fusarium species and chemotypes that can aid with the implementation of integrated disease management strategies to control the detrimental effects of this devastating disease.